Implementasi Kesadaran Hukum Lingkungan : Pengelolaan Sampah Plastik Melalui Partisipasi Mahasiswa - Syah Awaluddin; Andi Masniati; Rahmat Rahmat; M Zarsadin; Salsabilah Azzahra Tuasikal; Nivriawan Samoal; Rahmawati Tilaar (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This community service activity aims to increase the awareness of the community around the IAIN Ambon campus regarding the importance of plastic waste management and maintaining environmental cleanliness. Through the Participatory Action Research (PAR) method, students of the Islamic Criminal Law Study Program at the Faculty of Sharia IAIN Ambon acted as facilitators in the socialization and implementation of plastic waste recycling activities. This activity included education on the negative impacts of plastic waste, waste sorting practices, recycled product creation, and waste cleanup actions. The results showed positive changes in community behavior towards the environment and improved students' skills in applying the amar ma'ruf nahi munkar principle. This activity not only had a tangible social impact but also strengthened the application of Islamic values in the context of environmental preservation.